FIRE for the euro: A strategy for stabilizing government bond markets - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
The aggravating turbulences in the market for euro government bonds have so far precluded any recovery from the debt crisis. The key problem is that structural reforms and consolidation measures have long impact lags and are not able to stop an acute self-fulfilling crisis of confidence. In the discussion on possible solutions for this dilemma, Eurobonds and their numerous variants are prominent. – – Die Vertrauenskrise an den Märkten für Staatsanleihen sollte durch einen direkten Zinsausgleich bekämpft werden. Eine solche Lösungsoption zur Bekämpfung der europäischen Schuldenkrise vermeidet das Problem der Kollektivhaftung der Eurobonds und ist selbst bei Einbeziehung von Spanien und Italien bezahlbar. Zu diesem Ergebnis kommen Untersuchungen von Friedrich Heinemann, Forschungsbereichsleiter "Unternehmensbesteuerung und Öffentliche Finanzwirtschaft" am ZEW.
Keywords: 330